How to break the security-migration nexus and ensure a human-rights based management of international migration? - Sousa, Constança Urbano de (2019)
This article addresses the process of securitization of international migration in Europe, which has led to restrictive immigration policies, largely based on border control and restrictive legal migration pathways, which prevent or impede the migratory regularity of those foreigners in need of international protection, who want to reunite their families or have a reasonable prospect of finding better living conditions in the destination country. With the increasing nexus between migration and security, a vicious circle has been created that consolidates the perception of international migration as a threat to security, which, in turn, justifies more security measures and, with them, more dramatic flows of irregular migration. After putting international migration in general and the so-called "refugee crisis" in Europe, in particular, in perspective, in order to better understand its dimension, the second part of this article deals with the main elements of the process of securitization of migration in Europe and its consequences, such the promotion of irregular immigration and associated crimes, its artificial association with terrorism and crime and the sharpening of the polarization of Euro- pean societies. This, coupled with the absence of effective integration policies, boosted the growth of anti-immigrant sentiment, fuelled by the extreme-right’s populism, which explores people’s "fears" and endangers the civilizational values of modern democratic societies. The third part of this article seeks to answer the complex and difficult question of how to break the vicious circle of migratory irregularity and ensure a human-rights based management of legal migration.